2011
DOI: 10.1682/jrrd.2010.05.0089
|View full text |Cite
|
Sign up to set email alerts
|

Effect of home-based exercise program on lymphedema and quality of life in female postmastectomy patients: Pre-post intervention study

Abstract: Abstract-Lymphedema is a debilitating complication following mastectomy, affecting the arm functions and quality of life (QOL) of breast cancer patients. Studies have shown the beneficial effects of upper-limb exercises on lymphedema in clinical settings. However, there is a dearth of evidence regarding the effect of home-based exercises on lymphedema; therefore, we examined the effect of a home-based exercise program on lymphedema and QOL in postmastectomy patients. Thirty-two female postmastectomy lymphedema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
0
8

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 29 publications
(54 reference statements)
5
56
0
8
Order By: Relevance
“…These results are similar to those in other studies in which there was a statistically significant improvement at the 9th month after surgery in women with breast cancer who had the support of physiotherapy or an exercise program, when compared to women without the same type of support, in the scales of Global Health Status [24,27,52,53,54] and Arm Symptoms [54]. It should be noted that the studies by Travier et al [51] and Gordon et al [31] showed no statistically significant differences in the Global Health Status. In our study we registered a greater clinical improvement in the Experimental VS. Control Group in the scales of Physical Functioning, Future Perspective, Fatigue and Breast Symptoms, but without statistically significant differences.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These results are similar to those in other studies in which there was a statistically significant improvement at the 9th month after surgery in women with breast cancer who had the support of physiotherapy or an exercise program, when compared to women without the same type of support, in the scales of Global Health Status [24,27,52,53,54] and Arm Symptoms [54]. It should be noted that the studies by Travier et al [51] and Gordon et al [31] showed no statistically significant differences in the Global Health Status. In our study we registered a greater clinical improvement in the Experimental VS. Control Group in the scales of Physical Functioning, Future Perspective, Fatigue and Breast Symptoms, but without statistically significant differences.…”
Section: Discussionsupporting
confidence: 89%
“…In our study we registered a greater clinical improvement in the Experimental VS. Control Group in the scales of Physical Functioning, Future Perspective, Fatigue and Breast Symptoms, but without statistically significant differences. This matches some studies in which, in the 9th month after surgery, women with breast cancer undergoing physiotherapy or a specific exercise program presented better scores, but there were no statistically significant differences between groups, in the scales of Physical Functioning [21,31], Fatigue [21,51], and Breast Symptoms [31]. However, in other studies, in the same evaluation period, women with breast cancer who had the support of physiotherapy or an exercise program, when compared to women without that support, had statistically significant improvements in the scales of Physical Functioning [23,24,27 [21,52,53], and Breast Symptoms [27,28,30].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…8 Moreover, the upper limb movements during qigong exercise resemble the physiotherapeutic exercises used to reduce postsurgical lymphedema in breast cancer patients and survivors. 9 Therefore, we postulate that qigong may be a potentially beneficial exercise for survivors of breast cancer and could be used to regulate upper limb blood flow and decrease lymphedema. However, to our knowledge, there is no available evidence to inform health care professionals and patients of qigong's efficacy in relieving the surgical side effects of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps if the patients exercise for improving limb function, positive effects on quality of life would be observed. This has been approved by Gautam et al (22). As mentioned in the results, patients with grade III lymphedema showed no significant improvement in subscales of HRQoL after treatment except for PF.…”
Section: Discussionmentioning
confidence: 92%